Efficiency of autoregulatory homeostatic responses to imposed caloric excess in lean men. - Siervo, M; Frühbeck, G; Dixon, A; Goldberg, G; Coward, W; Murgatroyd, P; Prentice, A; Jebb, SA (2008)
Obesity implies a failure of autoregulatory homeostatic responses to caloric excess. We studied the mechanisms, effectiveness, and limits of such responses in six lean (21.9 +/- 1.3 kg/m(2)), healthy men based in a metabolic suite for 17 wk of progressive intermittent overfeeding (OF) (3 wk, baseline; 3 wk, 20% OF; 1 wk, ad libitum; 3 wk, 40% OF; 1 wk, ad libitum; 3 wk, 60% OF; 3 wk, ad libitum). Body composition was assessed by a four-compartment model using dual X-ray absorptiometry, deuterium dilution, and plethysmography. Magnetic resonance imaging assessed subcutaneous/visceral fat at abdominal level at baseline and at the end of 60% OF. Energy intake was assessed throughout, energy expenditure (EE) and substrate oxidation rates were measured repeatedly by whole body calorimetry (calEE), and free-living EE (TEE) was measured by doubly labeled water at baseline and after 60% OF. At the end of 60% OF, calEE and TEE had increased by just 11.4% (P = 0.001) and 16.2% (P = 0.001), respectively. Weight and body fat (fat mass) had increased by 5.98 kg (8.8%, P = 0.001) and 3.31 kg (22.6%, P = 0.01), respectively. The relative increase in visceral fat (32.6%, P = 0.02) exceeded that of subcutaneous fat (13.3%, P = 0.002) in the abdominal region. The computed energy cost of tissue accretion differed from the excess ingested by only 13.1% (using calEE) and 11.6% (using TEE), indicating an absence of effective dissipative mechanisms. We conclude that elevations in EE provide very limited autoregulatory capacity in body weight regulation, and that regulation must be dominated by hypothalamic modulation of energy intake. This result supports present conclusions from genetic studies in which all known causes of human obesity are related to defects in the regulation of appetite.